SAlBi educa (Tailored Nutrition App for Improving Dietary Habits): Initial Evaluation of Usability - Gonzalez-Ramirez, Marina; Cejudo-Lopez, Angela; Lozano-Navarrete, Mauricio; Salamero Sánchez-Gabriel, Elena; Torres-Bengoa, M. Alfonso; Segura-Balbuena, Manuel; Sanchez-Cordero, Maria J.; Barroso-Vazquez, Mercedes; Perez-Barba, Francisco J.; Troncoso, Ana M.; Garcia-Parrilla, M. Carmen; Cerezo, Ana B. (Frontiers in Nutrition, 2022)
In recent years, the use of applications to improve dietary habits has increased. Although numerous nutrition apps are available on the market, only few have been developed by health and nutrition professionals based on scientific evidence and subsequently tested to prove their usability. The main objective of this study was to design, develop and evaluate the usability of a tailored nutrition application to be used to promote healthy eating habits. In order to decide app design and content, three focus groups took place with fifteen professionals from primary healthcare, nutrition and food science and computer science, as well as expert users. For the general and feedback message design a reference model based on the scientific literature was developed. To address the multi-perspective approach of users' and external healthcare professionals’ feedback, a one-day pilot testing with potential users and healthcare professionals was conducted with four focus groups. To evaluate the relevance and potential usability of the app a one-month pilot test was conducted in a real-life environment. A total of 42 volunteers participated in the one-day pilot testing, and 39 potential users participated in the one-month pilot test. The SAlBi educa app developed includes an online dietary record, a self-monitoring tool to evaluate dietary patterns, general and feedback messages, and examples of traditional Mediterranean recipes. The usability study showed that volunteers think that SAlBi educa is pleasant (59 %) and easy to learn to use (94 %). Over 84% of the volunteers declared that the nutritional messages were clear and useful. Volunteers stated that general and tailored recommendations, as well as self-monitoring, were SAlBi educa’s most motivating and useful features. SAlBi educa is an innovative, user-friendly nutritional education tool with the potential to engage and help individuals to follow dietary habits based on the Mediterranean model.